A model-driven approach to enable the simulation of complex systems on distributed architectures. (December 2019) - Bocciarelli, Paolo; D'Ambrogio, Andrea; Falcone, Alberto; Garro, Alfredo; Giglio, Andrea
The increasing complexity of modern systems makes their design, development, and operation extremely challenging and therefore new systems engineering and modeling and simulation (M&S) methods, techniques, and tools are emerging, also to benefit from distributed simulation environments. In this context, one of the most mature and popular standards for distributed simulation is the IEEE 1516-2010 - Standard for M&S high level architecture (HLA). However, building and maintaining distributed simulations components, based on the IEEE 1516-2010 standard, is still a challenging and effort-consuming task. To ease the development of full-fledged HLA-based simulations, the paper proposes the MONADS method (MOdel-driveN Architecture for Distributed Simulation), which relies on the model-driven systems engineering paradigm. The method takes as input system models specified in Systems Modeling Language, the reference modeling language in the systems engineering field, and produces as output the final code of the corresponding HLA-based distributed simulation through a chain of model-to-model and model-to-text transformations. The obtained simulation code is based on the HLA Development Kit software framework, which has been developed by the SMASH-Lab (System Modeling and Simulation Hub - Laboratory) of the University of Calabria (Italy), in cooperation with the Software, Robotics, and Simulation Division (ER) of NASA's Lyndon B. Johnson Space Center (JSC) in Houston (TX, USA). The effectiveness of the method is shown through a case study that concerns a military patrol operation, in which a set of drones are engaged to patrol the border of a military area, in order to prevent both ground and flight attacks from entering the area.